Evaluation of the Precision of Phase-Measuring Bathymetric Side Scan Sonar Relative to Multibeam Echosounders - Pimentel, Vitor Bravo; Florentino, Christopher; Neto, Arthur Ayres (The International Hydrographic Review, 2020)
The International Hydrographic Organization (IHO) and the Directorate of Hydrography and Navigation (DHN) consider that where the under-keel clearance is critical, bathymetric surveys should provide full seafloor coverage. Multibeam Echosounders (MBES) and Phase-Measuring Bathymetric Side Scan (PMBS) are capable sensors to achieve this coverage, however, they have different technologies. The MBES is widely accepted by the international community and considered the standard system in surveys that require the highest IHO accuracy. The aim of this paper is to assess whether the PMBS can achieve comparable results with the MBES, focusing on Nautical Chart production. Despite “noisy” data and some effects, this research suggests that PMBS can be used to meet IHO requirements, under some special conditions.